Penerapan Teori Kriminologi Dalam Penanganan Kejahatan Seksual Oleh Anak - Widiyaswara, Riani; Maknun, Luil; Amin, Muhammad Nur (Sekolah Tinggi Ilmu Hukum Sumpah Pemuda, 2025)
This study aims to determine the causes of juvenile delinquency from the perspective of criminological theories. Studies on the theme of juvenile crime are always intertwined, whether the child is in the position of perpetrator, victim or witness. The perspectives used by researchers vary, ranging from substantive law or formal law to other disciplines relevant to legal studies, such as psychology and criminology. Criminology, which examines crime, has a very broad scope, with its subject matter covering crime and criminal behaviour. In this sense, criminology's study of crime is not limited to the act itself, as is the object of criminal law, but also views criminal acts as human behaviour. It even includes the study of social issues that tend to encourage criminal behaviour (criminogenic factors). The research method used was normative legal research using a legislative approach, theories and opinions of experts, and previous research on similar issues. The results of the study showed that criminal behaviour is identical to non-criminal behaviour, because both are learned. Edwin H. Sutherland hypothesised that criminal behaviour is learned through association with those who violate social norms, including legal norms. The understanding that the behaviour of lower-class delinquent children is a reflection of their dissatisfaction with the norms and values of middle-class children, who dominate the cultural values of society. It is recommended that in the future, the process of dealing with children in conflict with the law should involve all parties, from the government, law enforcement officials, the community and families.